KEMAMPUAN BATALYON KAVALERI 7/ PRAGOSA SATYA DALAM PENCEGAHAN RISIKO BENCANA SOSIAL DI DKI JAKARTA - Anak Agung Ngurah Sugiharto (Republic of Indonesia Defense University, 2023)
The Jakarta Capital Region is the Center of Gravity in Indonesia, and the threats around it are very high, one of which is social disaster. As a security unit for the capital city, and carries out OMSP's duties in disaster management. A unit must have strong capabilities, both human resources and technological resources, to help overcome social disasters that occur in DKI Jakarta. Therefore, to determine the capabilities of the 7th Cavalry Battalion/ Pragosa Satya, this research was conducted. The aim of this research is to analyze the condition of human resources and efforts to increase the capability of the 7th Cavalry Battalion/ Pragosa Satya to carry out the task of securing the capital city of Jakarta. The research method used in this research is qualitative with a phenomenological approach. The theory used in this research is Human Resource Management and the Concept of Improvement Strategy. The results of this research indicate that the condition of human resources and the facilities and infrastructure available are adequate in efforts to support social disaster management in DKI Jakarta. The conclusion of this research is, in an effort to increase the Battalion's capabilities, good human resource conditions can be utilized to face existing threats, and weaknesses can be minimized by continuing to improve competence so that increasing the Battalion's capabilities in the task of assisting in handling social disasters in DKI Jakarta can be carried out. well..